PENANGGULANGAN TERORISME DI INDONESIA MELALUI PENANGANAN PENDANAAN TERORISME: STUDI KASUS AL-JAMAAH AL-ISLAMIYAH (JI) - Safrudin, S.IP., M.Si. (Han), Rusli (Indonesia Defense University, 2013)
This article examines the efforts to combat terrorism in Indonesia through eradicating terrorist fund. There are some type of terrorist fund that is vulnerable to beused by terrorist organization like al-Jamaah al-Islamiyah (JI) in collecting and distributing its fundfor terror activity. This study is a qualitative research with descriptive analysis. This study follow Giovanni Manuntaâ€™s theory of relations between assets, frotection, threats, and vulnerability. The result of this study suggests the need to build mechanism of coordination and cooperation between stakeholders related with the efforts to prevent and eradicate terrorism fund in Indonesia.Â Keywords : terrorism, terrorism fund, al-Jamaah al Islamiyah (JI)